1966
DOI: 10.6028/jres.070a.037
|View full text |Cite
|
Sign up to set email alerts
|

Absolute isotopic abundance ratios and atomic weight of magnesium

Abstract: Absolute values have been obtained for the isotopic abundance ratios of magnesium, using surface e mi ss ion mas s spectrometry. Samples of known isotopic composition, prepared from nearly pure se parated magnesium isotopes, we re used to calibrate the mass spectrometers. The resulting abso· lute valu es are 25Mg/24Mg = 0.12663 ± 0.00013 and 26Mg/24Mg = 0 .13932 ± 0.00026, yielding an atomic weight (I2C = 12) of 24.30497 ± 0.00044. The indicated uncertainties are. ove.-. all limits of error based on 95 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
2

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(127 citation statements)
references
References 13 publications
5
118
2
Order By: Relevance
“…All whole-rock chondrites measured plot within ±0.01‰ Δ 25 Mg of the 334 terrestrial fractionation line, in keeping with other studies (Bizzarro et al, 2004;335 Young and Galy, 2004;Baker et al, 2005;Teng et al, 2010 (Catanzaro et al, 1966) and further 339 "external" normalisation of samples to bracketing standards (Table 1). These 340 chondritic mass independent Mg isotope ratios, average δ 26 Mg* = 0.0029 ± 0.017‰, 341 are indistinguishable from our terrestrial values, average = 0.0044 ± 0.022‰ (Thrane 342 et al, 2008).…”
Section: Chondrite Analyses 313supporting
confidence: 87%
“…All whole-rock chondrites measured plot within ±0.01‰ Δ 25 Mg of the 334 terrestrial fractionation line, in keeping with other studies (Bizzarro et al, 2004;335 Young and Galy, 2004;Baker et al, 2005;Teng et al, 2010 (Catanzaro et al, 1966) and further 339 "external" normalisation of samples to bracketing standards (Table 1). These 340 chondritic mass independent Mg isotope ratios, average δ 26 Mg* = 0.0029 ± 0.017‰, 341 are indistinguishable from our terrestrial values, average = 0.0044 ± 0.022‰ (Thrane 342 et al, 2008).…”
Section: Chondrite Analyses 313supporting
confidence: 87%
“…The upper bound of the standard atomic weight corresponds to magnesium in a specimen of olivine having a δ 26 Mg value of +1.03 ‰ relative to DSM3 [33]. The previous standard atomic-weight value A r (Mg) = 24.3050(6), recommended by the Commission in 1985 and published in "Atomic weights of the elements 1967" [2], was based on the "absolute" isotopic abundance measurements of Catanzaro et al [39], and Catanzaro and Murphy [40] found no evidence for variations in isotopic abundance in normal materials. Previous historical values of A r (Mg) include [20]: 1882, 24.01; 1894, 24.3; 1896, 24.29; 1897, 24.28; 1900, 24.3; 1903, 24.36; 1909, 24.32; 1961, 24.312; 1967, 24.305; 1969, 24. …”
Section: Magnesiummentioning
confidence: 99%
“…For the mono-collection mode, measured Mg-isotope ratios were corrected for mass fractionation (both instrumental and intrinsic) internally by a linear fractionation law normalized to the terrestrial Mg-isotope compositions ( 25 Mg/ 24 Mg = 0.12663, 26 Mg/ 24 Mg = 0.13932 (Catanzaro et al, 1966)). For the multicollection mode, instrumental mass fractionation was corrected by standard-sample bracketing assuming all terrestrial standards used have the terrestrial Mg-isotope compositions, and then intrinsic mass fractionation was corrected with a linear law.…”
Section: Introductionmentioning
confidence: 99%